Synthetic microbial consortium enhances acetoin production and functional quality of citrus vinegar via metabolic and process optimization - OuYang, Yerui; Zou, Shaoqing; Liu, Panpan; Xie, Linfeng; Xiao, Yiwen; Wang, Ya; Wu, Guangjie; Liu, Jiantao; Liu, Bin; Gao, Boliang; Zhu, Du (Frontiers in Microbiology, 2025)
Acetoin (3-hydroxy-2-butanone) is a key flavor compound that enhances the sensory profile of fruit vinegar. In this study, we developed a high-yield acetoin fermentation process using a synthetic microbial combination composed of Lactobacillus plantarum NF2 and Acetobacter pasteurianus NF171 for citrus vinegar production. By screening compatible strains and optimizing fermentation parameters, the co-culture system significantly improved acetoin synthesis compared to single-strain fermentations. Transcriptome analysis revealed that the consortium facilitated acetoin production by downregulating NADH metabolic flux and upregulating transcription of the α-acetyllactate synthase gene. Under optimized conditions—including 3% inoculum size, 120 rpm agitation, 33°C temperature, and 20 g/L sugar supplementation—the acetoin concentration reached 4033.72 ± 64.48 mg/L, representing an eight-fold increase over monoculture conditions. In addition to flavor enhancement, the process also enriched the vinegar with functional components, including acetic acid (57.91 ± 0.82 g/L), phenolic acids (such as chlorogenic and ferulic acids), and flavonoids (such as rutinarin and nobiletin). These compounds contribute to both product stability and potential health benefits. This study provides a practical and scalable strategy for enhancing acetoin biosynthesis and improving the quality of functional fruit vinegar through rational design of microbial consortia and process engineering.